Consideraciones sobre Infortunios de Alonso Ramírez - Taiano, Leonor (Nordlit, 2010)
This article attempts to provide new perspectives for approaching the study of Infortunios de Alonso Ramírez. Several researches about the text have given to Sigüenza y Góngora a character of strangeness to it, which would reduce him to the role of mere amanuensis, indicating that the discursive elaboration belongs to Ramirez. In view of that, I have performed a textual analysis, supported on the book's title and the final passage of the account, that I consider important elements that can offer a new perception on this issue. I base my research, additionally, on the study of its context of publication under the patronage of the New Spain viceroy, as well as the similarities of Infortunios de Alonso Ramírez with other contemporary texts.